Formulation of Flakes Bran Flour Substitution with Fortified Zinc for Fertile-Age Women - Ulfa, Atikah; Marjan, Avliya Quratul; Maryusman, Taufik (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2018)
There are about 32.9% Indonesian women susceptive to obesity and free radical exposure. Free radicals are resistible to Zn-cofactors and a-tocopherols. The aims of this study was to make flakes formulations with zinc fortification, then analyze the physical and chemical character of flakes (hardness and color degree), and analyze carbohydrate, protein, fat, zinc, and α-tocopherol. The experimental design used for this study was a complete randomized design. The results showed the best formulas that substitution by bran was 25 % and fortified seng was 118,9 mg. The chemical properties of the best formulas should has increased the levels of protein, fat, and Zinc. One serving (55g) of flakes has 208,4 Kal; 3,38 g protein; 0,27 g fat; 48,12 g carbohydrate ; 1,89 mg seng; and 3,53mg α-tocopherol.